Protection of Workers Rights Employment Copyrights and Laws - Suharno, FA Suharno; Rozikin, Imam; Felina, Felina (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
This research aims to determine the legal protection of workers' rights based on the Job Creation Law and the legal protection of the rights of workers of retirement age who remain employed. This research method uses normative juridical matters such as primary, secondary, and tertiary legal materials. The conclusion is that constitutional legal protection for workers is contained in Article 27 paragraph (2), Article 28D paragraph (1) and paragraph (2), Article 28H paragraph (3), and Article 28I (2) of the 1945 Constitution of the Republic of Indonesia. Concerning legal protection for workers work in International Covenants on Civil and Political Rights, as well as on Economic, Social and Cultural Rights. In the Job Creation Law, legal protection for workers is reflected in strategic policies in the employment sector, namely protecting and promoting the welfare of workers. Second, the absence of strict regulations regarding the retirement age limit in the Job Creation Law has an impact on the rights of workers who are still employed at retirement age, so there is no legal protection for those who are still employed at retirement age. As stated in the standard Employment Agreement, it does not fulfill the principle of freedom of contract and the principle of complete balance between Workers and Employers by the legal provisions of the agreement.